Enhanced drug loading efficiency of contact lenses via salt-induced modulation - Qiang Zhu; Shirui Mao (Elsevier, 2019)
Low drug loading efficiency is one of the main obstacles hindering the application of contact lenses (CLs) as the carrier for extended ocular drug delivery. Here in this study, a simple and effective drug loading method based on salt induced modulation was proposed and demonstrated with mechanism elucidation. First of all, using poly (2-hydroxyethyl methacrylate) (p-HEMA) as the contact lens material, betaxolol hydrochloride, Diclofenac Sodium and Betaxolol Base as the model drugs with different solubility, influence of salt concentration, salt type (sodium salts of sulfate, chloride, and sulfocyanate) and drug properties in the loading solution on drug loading efficiency was investigated. Mechanism of enhanced drug loading in contact lens was further explored via studying the influence of salt on the absorption isotherm, drug solubility and water content of CLs. Applicability of this method to other CLs materials was also investigated. It was demonstrated that adjusting the ionic strength of loading solutions resulted in significant increase of drug loading in CLs. Type and concentration of the salts and solubility of the drug were the main factors influencing enhancement ratio of drug loading. The mechanism for improved drug loading was related to the reduced drug solubility in loading solutions and the reduced bound water content in contact lenses. Modulation of drug loading by adjusting ionic strength was also applicable to other CLs and the light transmittance was not affected. This method was more suitable for salt-form drugs with high solubility. In summary, adjusting ionic strength of loading solution is an economical and effective way to improve drug loading in CLs, and this simple method may also find application in other hydrogel based drug delivery systems. Keywords: Contact lenses, Drug loading, Ionic strength, Absorption isotherms, Drug solubility, Bound water content